DISTRIBUSI INDUK UDANG GALAH (Macrobrachium rosenbergii) DI PANTAI TIMUR ACEH - Erlangga Erlangga (Berkala Perikanan Terubuk, 2016)
Aceh province has enormous fisheries potential, both freshwater and marine fisheries. one fishery biota which is featured prospect is prawns (Macrobrachium rosenbergii). Availability of the stock of prawns has been on the decline, and therefore this studied aims to determine the distribution of the existence of the brood stock prawns where located on the east coast of Aceh. This study used survey and analysis of water quality parameter. The results showed that on the east coast of Aceh where three districts that are in stock or distribution of prawns, Aceh Utaradistrict,Aceh Timurdistrictand Aceh Tamiang district. Aceh Utara district in the Tanah Pasir, Aceh Timur in the Peurelak and Aceh Tamiang in Seuruway. Distribution mains prawns in quality still showed a good result, but in terms of quantity was declining. The cause of the reduced number of prawns among other things because of the agricultural waste that causes pollution, because the region of Aceh are still many agricultural activities that still use pesticides. In addition due to fishing activities that use stun and tuba, very deadly existence of the stock of prawns are found in the waters of Aceh.